The Impact of Inject Chemical Neutralization toward the PH Change in the Reject Water Management on the Raw Water Treatment Facilities in Petrochemical Industries - Tutuka, Rachmadi; Ikhsandy, Ferry; Zulkipli, Rohiman Ahmad; Iman, Alamul; Arvianto, Rizky Ibnufaatih (Program studi Teknik Kimia UNS, 2025)
ABSTRACT. The water waste management in Petrochemical Industry becomes the significant challenge in maintain environmental quality—particularly in regulating pH levels in accordance with the standards set by Indonesia’s Ministry of Environment and Forestry Regulation No. 5 of 2014—chemical injection is widely employed. This method involves the addition of acidic or alkaline agents to neutralize the pH of reject water. This study evaluates the effect of varying chemical injection dosages to determine the optimal dose required to achieve a pH range of 6 to 9. The findings demonstrate a direct relationship between the increase in chemical injection dosage and changes in pH levels, where higher dosages consistently raised the pH, stabilizing at an average value of 8.2. Over a one-month monitoring period, the optimal dosage was identified as 0.085 m³, resulting in an average pH of 6.47. Excessive dosing is not only less effective but also led to increase operational costs, reaching up to IDR 872,235. Thus, optimizing chemical injection dosage is critical—not only for ensuring compliance with environmental pH standards but also for minimizing chemical consumption and reducing operational expenditures.Keywords:Inject chemicals, Wastewater treatment, pH, Reject water